2006
DOI: 10.1038/sj.onc.1210136
|View full text |Cite
|
Sign up to set email alerts
|

Mouse double minute antagonist Nutlin-3a enhances chemotherapy-induced apoptosis in cancer cells with mutant p53 by activating E2F1

Abstract: MDM2 is a critical negative regulator of the p53 tumor suppressor protein. Recently, small-molecule antagonists of MDM2, the Nutlins, have been developed to inhibit the p53-MDM2 interaction and activate p53 signaling. However, half of human cancers have mutated p53 and they are resistant to Nutlin treatment. Here, we report that treatment of the p53-mutant malignant peripheral nerve sheath (MPNST) and p53-null HCT116 cells with cisplatin (Cis) and Nutlin-3a induced a degree of apoptosis that was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
129
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 33 publications
13
129
1
1
Order By: Relevance
“…This relative difference in Nutlin efficacy based on p53 status is consistent with previous reports (Van Maerken et al, 2006;Ambrosini et al, 2007). Although the inhibition constant (K i ) is reported to be 0.09 mM for Nutlin-3a (Vassilev et al, 2004) and 0.7 mM for Nutlin-3 (Laurie et al, 2006) in p53 wt cells in vitro, numerous studies have reported that 10 mM of Nutlin-3 or Nutlin-3a is needed to disrupt the p53-HDM2 complex and elicit maximal downstream effects in vivo (Vassilev et al, 2004;Laurie et al, 2006;Patton et al, 2006;Tovar et al, 2006;Larusch et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This relative difference in Nutlin efficacy based on p53 status is consistent with previous reports (Van Maerken et al, 2006;Ambrosini et al, 2007). Although the inhibition constant (K i ) is reported to be 0.09 mM for Nutlin-3a (Vassilev et al, 2004) and 0.7 mM for Nutlin-3 (Laurie et al, 2006) in p53 wt cells in vitro, numerous studies have reported that 10 mM of Nutlin-3 or Nutlin-3a is needed to disrupt the p53-HDM2 complex and elicit maximal downstream effects in vivo (Vassilev et al, 2004;Laurie et al, 2006;Patton et al, 2006;Tovar et al, 2006;Larusch et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, our Nutlin-3 activates p73 LMS Lau et al data demonstrate that Nutlin-3 alone induces p73 protein stabilization as well as enhanced TAp73 transcriptional activity. Thus, the increase in E2F-1 transcriptional activity and p73 protein levels reported by Ambrosini et al (2007) is likely due to the combination treatment with cisplatin chemotherapy and Nutlin-3 since chemotherapies including cisplatin and doxorubicin are known to activate both E2F1 and TAp73 (Irwin, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25,26 E2F-1 differs from that of other E2F family members due to its ability to regulate not only cell-cycle progression but also apoptosis as it directly induces the expression of p73, of caspase 3 and 7 and of some pro-apoptotic Bcl-2 family members. [27][28][29][30][31][32][33][34] We show here that E2F-1 is a major contributor of caspase-dependent induction of Noxa in response to ABT-737 treatment. Caspases cleave the E2F-1 regulator pRb in ABT-737-treated cells, giving rise to a p68Rb truncated form, which has a direct role in Noxa and cell death inductions together with E2F-1.…”
mentioning
confidence: 51%
“…As treatment with the Mdm2 inhibitor Nutlin-3a was shown to enhance the pRb/E2F-1 pathway, 33,34 we reasoned that it may increase cell sensitivity to ABT-737, provided pRb is present. We found that combination of Nutlin-3a to ABT-737, but not treatment with anyone alone, induced dramatic cell death in the breast cancer cell lines MDA-MB-231 and MDA-MB-468, cells that carry p53 mutations (R280K and R273H, respectively) and constitutively express low levels of pRb (Figures 8a and b).…”
mentioning
confidence: 99%